Biological effects of oxidants and antioxidants in clinical diagnosis of diseases: A review - VIJAYALAKSHMI, B; CHANDRASEKHAR, M (The Indian Journal of Animal Sciences, 2011)
Oxidative stress is commonly defined as an imbalance between oxidants and reductants (antioxidants) at the cellular or individual level. Oxidative damage is result of such an imbalance and includes oxidative modification of cellular macromolecules, cell death by apoptosis or necrosis, as well as structural tissue damage. The imbalance can result from a lack of antioxidant capacity caused by disturbance in production, distribution, or by an overabundance of ROS from an environmental or behavioral stress. If not regulated properly, the excess ROS damages polyunsaturated fatty acids found in the cellular membranes, nucleotides in the DNA, and sulfhydril bonds in proteins. Nearly every organ system can be found to have an oxidative stress. Certain organ systems are predisposed to greater levels of oxidative stress. Those organ systems most susceptible to damage are the pulmonary system (exposed to high levels of oxygen), the brain (exhibits intense metabolic activity yet has lower levels of endogenous antioxidants), the eye (constantly exposed to damaging UV light), circulatory system (victim to fluctuating oxygen and nitric oxide levels) and reproductive systems (at risk from the intense metabolic activity of sperm cells). Oxidative damage causes a net stress on the normal body functions and may result in many specific diseases. It also appears to contribute to the general decline in the optimum body functions that is commonly believed to occur as a result of aging process. So, there is a need to continuously monitor the level of oxidants and antioxidants in the body to overcome the oxidative stress. This paper reviews on oxidative stress, counter action of antioxidants, and methods to monitor the oxidants and antioxidants.